Birds of the Patos Lagoon Estuary and adjacent coastal waters, southern Brazil: species assemblages and conservation implications. Issue 1 (2nd January 2017) - Dias, Rafael Antunes; Maurício, Giovanni Nachtigall; Bugoni, Leandro
ABSTRACT: Estuarine avifauna is usually diverse, with marked differences along the limnetic to marine gradient and strong influences from physical factors such as salinity, habitat heterogeneity and tidal regime. Here we describe the composition of the avifauna of the Patos Lagoon Estuary and adjacent marine beaches and waters, in southern Brazil, identify the main environmental factors determining variations in species richness along the limnetic-marine gradient, evaluate changes in species composition along this gradient, and discuss the role of the estuary for bird conservation. Overall, 268 bird species were detected at eight sites along the estuary. Despite similar observed richness in spring–summer (247 species) and autumn–winter (244), there was a strong seasonal influence in bird composition due to migrants. Estimated species richness at 94% coverage of sites ranged from 9 to 194.66. Species richness decreased markedly towards the lower estuary, with the single variable 'distance from the upper estuary', accounting for the most plausible model. The number of threatened species recorded per site was larger in the lower estuary due the predominance of seabirds and shorebirds on red lists. While the lower estuary holds key feeding and roosting areas for seabirds and shorebirds, the upper estuary harbours more species, mainly forest passerines and waterbirds. Our findings confirm that estuarine gradients strongly influence avian diversity and highlight the importance of estuaries for the conservation of birds, especially migratory sea and shorebirds, and resident saltmarsh-dependent species.